High-entropy alloy nano iridium-based catalyst as well as preparation method and application thereof
By accurately controlling seven metal elements on the nanoscale, forming core-shell icosahedral seven-membered metal nanocrystals and high-entropy alloy nanocage iridium-based catalysts, the existing iridium-based catalysts are solved. The activity and stability of existing iridium-based catalysts in acidic environments are low. The problem is that efficient and stable acidic OER catalytic performance is achieved, and is suitable for PEMWE hydrogen production.
Patent Information
- Application Number
- CN202411719749.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2025-02-14
AI Technical Summary
The existing iridium-based catalysts have low OER activity and stability in acidic environments, limiting their large-scale application in PEMWE.
By accurately controlling seven metal elements on the nanoscale, forming core-shell icosahedral seven-membered metal nanocrystals and high-entropy alloy nanocage iridium-based catalysts, the regulation of the electronic structure of iridium active sites and the precise regulation of specific exposed surfaces is achieved. .
It significantly improves the acidic OER activity and stability of the catalyst, reduces the amount of precious metals, achieves efficient catalytic performance and excellent stability, and is suitable for PEMWE hydrogen production.
Smart Images

Figure HDA0005157742230000011 
Figure HDA0005157742230000012 
Figure HDA0005157742230000013
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of oxygen evolution reaction (OER) catalysts, and specifically relates to a high entropy alloy nano-iridium-based catalyst and a preparation method and application thereof. Background Art
[0002] Proton exchange membrane hydrolyzer (PEMWE) is an attractive technology for renewable energy conversion and storage. Compared with other water electrolysis hydrogen production technologies, PEMWE hydrogen production has several key advantages, such as a fast response time (<10s), a high operating current density (>2Acm -2 ), higher hydrogen purity (>99.99vol%). Due to the lower pH value in its cathode, PEMWE can avoid the slow hydrogen evolution reaction kinetics in alkaline electrolytes and exhibit high hydrogen production performance. In addition, the high current density prevents the formation of pollutants such as carbonates, thereby extending the cycle life of PEMWE. However, the slow OER kinetics and locally corrosive operating environment in PEMWE place strict requirements on the development of anode electrocatalysts, which in turn affects the large-scale application of PEMWE. Therefore, it is necessary and extremely challenging to develop an acidic OER catalyst with both high activity and stability.
[0003] At present, most research focuses on the development of precious metal ruthenium and iridium-based OER catalysts. However, the harsh acidic environment and high current density will cause severe precipitation of ruthenium-based materials, resulting in a rapid decrease in activity and stability, which is not suitable for practical application in PEMWE. Since iridium-based catalysts can withstand long-term operation in acidic environments without severe corrosion or performance degradation, they are still the main OER catalysts compatible with PEMWE. Nevertheless, the limited intrinsic OER activity, high loading requirements and actual scarcity of iridium-based catalysts in PEMWE limit their large-scale application. Therefore, the development of an iridium-based catalyst that is both efficient, stable and cost-effective has become one of the research focuses.
[0004] The alloying strategy is to mix two or more metal elements at the nanoscale to form a noble metal catalytic material with high catalytic performance and economic benefits. Among them, high entropy alloys composed of at least five metal elements (5-35at.%) break the narrow ratio limit of traditional alloys and provide a strategy for noble metal catalytic materials with excellent catalytic performance, high stability and economic benefits. However, most of the reported high entropy alloy nanomaterials show the morphological characteristics of spherical nanoparticles. In fact, the catalytic performance of nanoparticles is highly dependent on their shape, size and surface roughness, which affect their active area and electron / mass transfer efficiency, and then act on reaction kinetics and catalytic activity. Therefore, it is necessary to develop high entropy alloy nanocrystals with specific morphology, which provides an exemplary research framework for exploring the connection between structure and performance.
[0005] Huang Xiaoqing's research group (Subnanometer High-Entropy Alloy Nanowires EnableRemarkable Hydrogen Oxidation Catalysis. Nature Communications, 2021, 12: 6261) obtained lattice mismatched PtRuNiCoFeMo sub-nanowires with rich atomic steps and defects through a one-pot method. Compared with the corresponding nanoparticles, the high-entropy alloy with one-dimensional nanowire morphology exhibits excellent hydrogen oxidation activity and carbon monoxide tolerance. In addition, the PtMoPdRhNi nanoflowers assembled by two-dimensional nanosheets can greatly improve the utilization rate of precious metals and the effective proton transfer efficiency, achieving excellent catalytic performance that the corresponding high-entropy alloy nanoparticles cannot achieve (High-entropy alloy nanocrystal assembled by nanosheets with dd electron interaction for hydrogen evolution reaction. Energy & Environmental Science, 2023, 16 (9): 4009-19). The Yamauchi group (Mesoporous multimetallic nanospheres with exposed highlyentropic alloy sites. Nature Communications, 2023, 14(1):12) synthesized PtPdRhRuCu mesoporous nanospheres using block copolymer micelles as soft templates. The unique mesoporous effect provides abundant channels for the adsorption and deep diffusion of reactants inside the nanospheres, while the large number of atomic steps and kinks on the surface provide a large number of active sites to achieve efficient alkaline hydrogen evolution.
[0006] However, the current synthesis strategies of high-entropy alloy polyhedra are focused on high-temperature chemical methods such as dealloying, and the size of the produced high-entropy alloys is relatively large, which is not conducive to the catalytic reaction. The polyhedral morphologies of tetrahedrons, octahedrons, dodecahedrons, and icosahedrons synthesized by wet chemical methods have achieved remarkable results in the fields of single metals and binary alloys. However, given the different nucleation and growth kinetics of different metal components in high-entropy alloys, it has become a major problem that researchers need to solve to precisely control the reduction and growth of five or more metal elements at the nanoscale to form a specific morphology and to finely regulate the growth of specific exposed surfaces.
[0007] The present invention successfully prepares a core-shell icosahedral seven-element metal nanocrystal and a high entropy alloy nanocage iridium-based catalyst by a certain method. The iridium-based high entropy alloy catalyst contains up to seven metal elements. The present invention realizes effective regulation of the electronic structure of the iridium active site, while reducing costs and improving catalytic efficiency. It also realizes precise regulation of specific exposed surfaces, further improving the performance of the iridium-based catalyst and optimizing the utilization efficiency of precious metals. The catalyst of the present invention has a good effect in electrocatalysis, especially in PEMWE hydrogen production. Summary of the invention
[0008] The present invention provides a high entropy alloy nano-iridium-based catalyst and a preparation method and application thereof. The catalyst of the present invention comprises one or more of a core-shell icosahedral seven-element metal nanocrystal and a high entropy alloy nanocage supported on a carbon nanotube. The present invention prepares a core-shell icosahedral seven-element metal nanocrystal and a high entropy alloy nanocage iridium-based catalyst by precisely controlling seven metal elements at the nanoscale to form a specific morphology and carefully regulating the growth of a specific exposed surface, thereby solving the problems of low OER activity and stability of existing iridium-based catalysts in an acidic environment.
[0009] The purpose of the present invention is achieved through the following technical solutions:
[0010] A method for preparing a high entropy alloy nano-iridium-based catalyst comprises the following steps:
[0011] (S1) Preparation of core-shell icosahedral PdCu@IrPdCuFeNiCoMo / CNTs;
[0012] Under a protective atmosphere, a mixture obtained by mixing hexadecyltrimethylammonium chloride, oleylamine, glucose, carbon nanotubes and transition metal salt is heated to obtain core-shell icosahedral nanocrystals; the heating treatment refers to stirring at 255-265° C. for 1.5-2.5 hours, preferably 100-135 minutes, more preferably 110-130 minutes; the stirring speed is 600-700 rpm, preferably 600-660 rpm;
[0013] The heating treatment refers to heating the mixture at 15-25°C·min under stirring. -1 The heating rate is from room temperature to 255-265°C, and then kept warm for 1.5-2.5 hours;
[0014] The transition metal salt is palladium acetylacetonate, copper acetylacetonate, iridium acetylacetonate, iron acetylacetonate, nickel acetylacetonate, cobalt acetylacetonate and molybdenum hexacarbonyl.
[0015] Alternatively, the preparation method also includes (S2) preparation of high entropy alloy nanocages IrPdCuFeNiCoMo-NCs / CNTs; specifically, dispersing core-shell icosahedral nanocrystals in water containing polyvinyl pyrrolidone to obtain solution A; dissolving ferric chloride, potassium bromide and concentrated hydrochloric acid in water to obtain solution B; adding solution A to solution B, mixing by ultrasonic treatment, and then heating and stirring to obtain a high entropy alloy nanocage iridium-based catalyst.
[0016] The molar ratio of palladium acetylacetonate, copper acetylacetonate, iridium acetylacetonate, iron acetylacetonate, nickel acetylacetonate and cobalt acetylacetonate in step (S1) is (0.9-1.1): (0.9-1.1): (0.9-1.1): (0.9-1.1): (0.9-1.1): (0.9-1.1), preferably 1:1:1:1:1:1; the molar ratio of palladium acetylacetonate to molybdenum hexacarbonyl is (0.036-0.04) mmol: (0.16-0.18) mmol; the palladium acetylacetonate: The molar mass ratio of glucose: carbon nanotubes: hexadecyltrimethylammonium chloride is (0.036-0.04) mmol: (95-105) mg: (52-60) mg: (95-105) mg; the mass ratio of glucose: carbon nanotubes is preferably (95-105) mg: (53.6-59.6) mg; the mass volume ratio of hexadecyltrimethylammonium chloride to oleylamine is (95-105) mg: (25-35) mL, preferably (95-105) mg: (28-32) mL.
[0017] The mixture in step (S1) is prepared by dissolving hexadecyltrimethylammonium chloride in oleylamine to obtain a hexadecyltrimethylammonium chloride mixed solution; mixing glucose, carbon nanotubes and transition metal salt, and then ultrasonically mixing the mixed solution with the hexadecyltrimethylammonium chloride to obtain a mixture.
[0018] The ultrasonic mixing time is 1.5 to 2.5 hours, and the ultrasonic frequency is 32 to 48 kHz.
[0019] In step (S1), the process of "under protective atmosphere" refers to removing oxygen from the mixture and introducing protective gas. Specifically, the process of vacuumizing, introducing protective gas, vacuumizing, introducing protective gas, repeating the process, removing oxygen from the mixture and introducing protective atmosphere. The time of vacuumizing and introducing protective gas is 4 to 6 minutes.
[0020] After the heating treatment in step (S1), subsequent treatment is performed; the subsequent treatment refers to cooling, centrifugation, washing the precipitate with a cyclohexane / ethanol mixed solution; then the precipitate is soaked in an acetic acid ethanol solution, centrifuged, washed with anhydrous ethanol, and dried.
[0021] (S1) is cooled, and during centrifugation, the centrifugal speed is 9600-10000 rpm, the cyclohexane / ethanol volume ratio is 1:4-6, and the number of washing times is 2-5 times.
[0022] The concentration of the acetic acid ethanol solution is 0.4-0.6 mol / L, and the soaking treatment conditions are: soaking at 40-60°C for 2.5-3.5 hours, preferably 2.7-3.3 hours. After the soaking treatment, the centrifugal speed is 8500-9500 rpm, the number of washings is 1-3 times, the vacuum drying temperature is 55-65°C, and the drying time is 11.5-12.5 hours.
[0023] In step (S2), the mass ratio of the core-shell icosahedral nanocrystals to ferric chloride is (18-22): (145-155); the mass ratio of the core-shell icosahedral nanocrystals to polyvinyl pyrrolidone is (18-22): (245-255); the mass volume ratio of polyvinyl pyrrolidone to water in the solution A is (245-255) mg: (10-15) mL, preferably (245-255) mg: (11-13) mL. The molecular weight of polyvinyl pyrrolidone is 54,000-56,000.
[0024] In solution B, the mass ratio of ferric chloride to potassium bromide is (145-155):(595-605); the mass volume ratio of ferric chloride to concentrated hydrochloric acid is (145-155) mg:(0.8-1) mL, and the mass fraction of concentrated hydrochloric acid is 36%; the mass volume ratio of ferric chloride to water is (145-155) mg:(17-19) mL.
[0025] The heating and stirring temperature in step (S2) is 97-103° C., the heating and stirring time is 0.48-0.52 hours; the stirring speed is 780-840 rpm; and the ultrasonic mixing time is 19-21 minutes.
[0026] The frequency of the ultrasound is 36-44 kHz.
[0027] After heating and stirring in step (S2), subsequent treatment is performed; the subsequent treatment is centrifugation, washing, and drying; the centrifugation speed is 8800-9200 rpm, the number of washings is 2-4 times, the vacuum drying temperature is 55-65°C, and the drying time is 11.5-12.5 hours.
[0028] The iridium-based catalyst includes one or more of core-shell icosahedral PdCu@IrPdCuFeNiCoMo / CNTs or high entropy alloy nanocages IrPdCuFeNiCoMo-NCs / CNTs.
[0029] The iridium-based catalyst is used in oxygen evolution reaction, especially in OER under acidic environment.
[0030] Application of the iridium-based catalyst in proton exchange membrane electrolysis of water.
[0031] Compared with the prior art, the present invention has the following beneficial effects:
[0032] Compared with binary and ternary iridium-based alloy catalysts, the iridium-based high-entropy alloy catalyst obtained by the present invention contains up to seven metal elements, and is a high-entropy alloy nanocage formed by further selective etching of core-shell icosahedral nanoparticles loaded on carbon nanotubes; the surface of the core-shell icosahedron is rich in twin boundaries, and the surface atoms in these interface areas have a low chemical coordination number, which can significantly improve the catalytic activity; and the further prepared nanocage structure not only has a larger specific surface area and open porous channels, but also contains rich surface strain, which provides a large number of active sites for efficient transfer of surface charges and catalytic reactions; alloying iridium with cheap transition metals can adjust the central site electronic structure of the high-entropy alloy, reduce the energy barrier of the key steps of the reaction process, and effectively reduce the amount of iridium used, achieving ultra-high mass activity and excellent stability with extremely low precious metal loading.
[0033] For example, the acidic OER overpotential of the PdCu@IrPdCuFeNiCoMo / CNTs catalyst of the present invention is 251 / 307 mV (10 / 50 mA·cm -2 ), the overpotential of acidic OER of IrPdCuFeNiCoMo-NCs / CNTs catalyst is 235 / 282 mV (10 / 50 mA·cm -2 ); PdCu@IrPdCuFeNiCoMo / CNTs and IrPdCuFeNiCoMo-NCs / CNTs catalysts at 1.50V RHE Under the condition of high temperature, the 1624 and 662A g Ir -1The acidic OER mass activity of PdCu@IrPdCuFeNiCoMo / CNTs and IrPdCuFeNiCoMo-NCs / CNTs catalysts, respectively, was assembled into a proton exchange membrane hydrolyzer as anode catalyst at 500 mA cm -2 At 65°C and 125°C, it exhibits excellent stability of over 450 and 900 hours respectively. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 Schematic diagram of the characterization of the PdCu@IrPdCuFeNiCoMo / CNTs core-shell icosahedral seven-membered metal nanocrystal catalyst in Example 1; high-angle annular dark-field transmission electron microscopy images are (a) and (b), the transmission electron microscopy image is (c), the X-ray diffraction image is (d), and the element distribution diagram is (e).
[0035] Figure 2 Schematic diagram of the characterization of the IrPdCuFeNiCoMo-NCs / CNTs high entropy alloy nanocage catalyst in Example 2; high-angle annular dark field transmission electron microscopy images are (a) and (b), transmission electron microscopy image is (c), X-ray diffraction image is (d), and element distribution map is (e).
[0036] Figure 3 Schematic diagram of the characterization of the Pd@IrPdFeNiCoMo / CNTs core-shell nanocrystal catalyst in Comparative Example 1, including a transmission electron microscope image (a), high-angle annular dark field transmission electron microscope images (b) and (c), an X-ray diffraction image (d), and an element distribution diagram (e).
[0037] Figure 4 Schematic diagram of the characterization of the Cu@IrCuFeNiCoMo / CNTs core-shell nanocrystal catalyst in Comparative Example 2; high-angle annular dark-field transmission electron microscopy images are (a), (b) and (c), the X-ray diffraction pattern is (d), and the element distribution diagram is (e).
[0038] Figure 5 Figure 1 is a characterization diagram of acidic OER performance; the polarization curves of the catalysts and the reference sample iridium dioxide in Example 1, Example 2, Comparative Example 1, Comparative Example 2 are (a), the overpotential comparison at different current densities is (b), the Tafel slope diagram is (c), the polarization curve normalized by the electrochemical active surface area is (d), 1.50V RHE The comparison of mass activity and specific activity is (e), and the electrochemical impedance spectrum is (f).
[0039] Figure 6is a PEMWE performance characterization diagram; the schematic diagram of the PEMWE device is (a), and the polarization curves of the core-shell icosahedral seven-element metal nanocrystals in Example 1, the high entropy alloy nanocages in Example 2, and the reference sample iridium dioxide as anode catalyst are (b), 1.0 / 2.0 A·cm -2 Comparison of battery voltage at (c), 65℃@500mA·cm -2 The chronopotentiometry curve below is (d). DETAILED DESCRIPTION
[0040] The present invention is further described below in conjunction with the accompanying drawings and embodiments. The embodiments of the present invention include but are not limited to the following embodiments.
[0041] Example 1
[0042] S1: Dissolve 100 mg of hexadecyltrimethylammonium chloride in a flask containing 30 mL of oleylamine and sonicate for 30 minutes;
[0043] S2: 100 mg of glucose, 56.6 mg of carbon nanotubes, 11.6 mg of palladium acetylacetonate, 10.0 mg of copper acetylacetonate, 18.6 mg of iridium acetylacetonate, 13.4 mg of iron acetylacetonate, 9.8 mg of nickel acetylacetonate, 9.8 mg of cobalt acetylacetonate, and 45 mg of molybdenum hexacarbonyl were weighed into a mortar, ground for 20 minutes, added to the above flask, and further sonicated for 2 hours until the mixture was uniformly mixed;
[0044] S3: Place the flask in a heating mantle and keep stirring. At room temperature, evacuate for 5 minutes, pass Ar gas for 5 minutes, and repeat the steps three times. After completing the above steps, set the stirring speed of the heating mantle to 630 rpm, the target temperature to 260°C, start heating, and keep the temperature for 2 hours after reaching the target temperature.
[0045] S4: After naturally cooling to room temperature, the precipitate was collected by centrifugation and washed three times by centrifugation with a cyclohexane / ethanol mixed solution with a volume ratio of 1:5, and the centrifugal speed was 9800 rpm; then 0.5 mol / L acetic acid ethanol solution was added, kept at 50°C for 3 hours, the precipitate was collected by centrifugation, and washed twice by centrifugation with anhydrous ethanol, and the centrifugal speed was 9000 rpm; vacuum dried at 60°C to obtain PdCu@IrPdCuFeNiCoMo / CNTs.
[0046] Example 2
[0047] S1: 20 mg of PdCu@IrPdCuFeNiCoMo / CNTs prepared in Example 1 was dispersed in 12 mL of deionized water containing 250 mg of polyvinyl pyrrolidone (molecular weight 55000), which was recorded as solution A; then, 150 mg of ferric chloride, 600 mg of potassium bromide and 0.9 mL of concentrated hydrochloric acid (mass fraction 36%) were added to 18 mL of deionized water, which was recorded as solution B; under ultrasonic conditions, solution A was dripped into solution B at one time, and further ultrasonicated for 20 minutes to mix them evenly;
[0048] S2: The stirring rate was set to 810 rpm, and the mixed solution was kept at 100°C for 0.5 h. Finally, the precipitate was collected by centrifugation and washed three times with deionized water at a centrifugal speed of 9000 rpm. The product was vacuum dried at 60°C and was recorded as IrPdCuFeNiCoMo-NCs / CNTs.
[0049] Comparative Example 1
[0050] S1: Dissolve 100 mg of hexadecyltrimethylammonium chloride in a flask containing 30 mL of oleylamine and sonicate for 30 minutes;
[0051] S2: 100 mg of glucose, 56.6 mg of carbon nanotubes, 11.6 mg of palladium acetylacetonate, 18.6 mg of iridium acetylacetonate, 13.4 mg of iron acetylacetonate, 9.8 mg of nickel acetylacetonate, 9.8 mg of cobalt acetylacetonate, and 45 mg of molybdenum hexacarbonyl were weighed into a mortar, ground for 20 minutes, added to the above flask, and further sonicated for 2 hours until the mixture was uniformly mixed;
[0052] S3: Place the flask in a heating mantle and keep stirring. At room temperature, evacuate for 5 minutes, pass Ar gas for 5 minutes, and repeat the steps three times. After completing the above steps, set the stirring speed of the heating mantle to 630 rpm, the target temperature to 260°C, start heating, and keep the temperature for 2 hours after reaching the target temperature.
[0053] S4: After naturally cooling to room temperature, the precipitate was collected by centrifugation and washed three times by centrifugation with a cyclohexane / ethanol mixed solution with a volume ratio of 1:5 at a centrifugal speed of 9800 rpm; then 0.5 mol / L acetic acid ethanol solution was added and kept at 50°C for 3 hours, the precipitate was collected by centrifugation, washed twice by centrifugation with anhydrous ethanol at a centrifugal speed of 9000 rpm, and vacuum dried at 60°C to obtain Pd@IrPdFeNiCoMo / CNTs.
[0054] Comparative Example 2
[0055] S1: Dissolve 100 mg of hexadecyltrimethylammonium chloride in a flask containing 30 mL of oleylamine and sonicate for 30 minutes;
[0056] S2: 100 mg of glucose, 56.6 mg of carbon nanotubes, 10.0 mg of copper acetylacetonate, 18.6 mg of iridium acetylacetonate, 13.4 mg of iron acetylacetonate, 9.8 mg of nickel acetylacetonate, 9.8 mg of cobalt acetylacetonate, and 45 mg of molybdenum hexacarbonyl were weighed into a mortar, ground for 20 minutes, added to the above flask, and further sonicated for 2 hours until the mixture was uniformly mixed;
[0057] S3: Place the flask in a heating mantle and keep stirring. At room temperature, evacuate for 5 minutes, pass Ar gas for 5 minutes, and repeat the steps three times; after completing the above steps, set the stirring speed of the heating mantle to 630rpm, the target temperature to 260℃, start heating, and keep it at the target temperature for 2 hours;
[0058] S4: After naturally cooling to room temperature, the precipitate was collected by centrifugation and washed three times by centrifugation with a cyclohexane / ethanol mixed solution with a volume ratio of 1:5 at a centrifugal speed of 9800 rpm; then 0.5 mol / L acetic acid ethanol solution was added and kept at 50°C for 3 hours, the precipitate was collected by centrifugation, washed twice by centrifugation with anhydrous ethanol at a centrifugal speed of 9000 rpm, and vacuum dried at 60°C to obtain Cu@IrCuFeNiCoMo / CNTs.
[0059] Material structure characterization:
[0060] Figure 1 Schematic diagram of the characterization of the PdCu@IrPdCuFeNiCoMo / CNTs core-shell icosahedral seven-membered metal nanocrystal catalyst in Example 1; high-angle annular dark field transmission electron microscopy images are (a) and (b), transmission electron microscopy image is (c), X-ray diffraction image is (d), and element distribution map is (e). Figure 1 As can be seen from Figures a and b, the nanoparticles are evenly distributed on the carbon nanotubes, with an average axial size of 16.2±2.9nm. Figure 1 Figure c in the middle reveals the characteristics of icosahedral nanocrystals. Figure 1 The X-ray diffraction peak position in (d) was corrected by aluminum foil, showing its face-centered cubic (FCC) crystal phase. Figure 1 The element mapping distribution in the middle e shows that palladium and copper are mainly distributed in the core site of the icosahedron, while a small amount of palladium and copper as well as iridium, iron, nickel, cobalt and molybdenum are distributed in the shell site, proving the formation of PdCu core@IrPdCuFeNiCoMo high-entropy alloy shell nanocrystals.
[0061] Figure 2 Schematic diagram of the characterization of the IrPdCuFeNiCoMo-NCs / CNTs high entropy alloy nanocage catalyst in Example 2; high-angle annular dark field transmission electron microscopy images are (a) and (b), transmission electron microscopy image is (c), X-ray diffraction image is (d), and element distribution map is (e). Figure 2Figures a and b show a hollow nanocage structure with an average axial size of 17.5±3.7 nm. Figure 2 Figure c shows a lattice spacing of 0.210 nm, corresponding to the (111) lattice of the FCC phase. Figure 2 The X-ray diffraction pattern in (d) shows the FCC crystalline phase. Figure 2 The dark field image in middle e shows defects on the surface of the hollow nanocages, and the element mapping shows that all elements are uniformly distributed throughout the nanocage, indicating the formation of IrPdCuFeNiCoMo high-entropy alloy nanocages.
[0062] Comparative Example 1 was further implemented, i.e., the copper precursor was removed without changing other synthesis conditions, to explore the important influence of the copper element on the morphology and properties of the icosahedron. Figure 3 Schematic diagram of the characterization of the Pd@IrPdFeNiCoMo / CNTs core-shell nanocrystal catalyst in Comparative Example 1, including a transmission electron microscope image (a), high-angle annular dark field transmission electron microscope images (b) and (c), an X-ray diffraction image (d), and an element distribution diagram (e). Figure 3 The middle ac images show irregular nanocrystals with an average size of 14.9 ± 2.1 nm, a rough surface and severe agglomeration. Figure 3 The element mapping distribution diagram in e clearly shows that palladium is mainly distributed in the core, while iridium, iron, nickel, cobalt, molybdenum and part of palladium are distributed in the shell, proving the formation of Pd core@IrPdFeNiCoMo high-entropy alloy shell nanocrystals. Figure 3 The X-ray diffraction pattern in the figure shows two main crystal phases, namely the FCC crystal phase of Pd in the core and the FCC crystal phase of IrPdFeNiCoMo high-entropy alloy in the shell, which further proves the generation of Pd@IrPdFeNiCoMo nanocrystals.
[0063] Next, Comparative Example 2 was implemented, i.e., the palladium precursor was removed without changing other synthesis conditions, in order to explore the important influence of the palladium element on the morphology and performance of the icosahedron. Figure 4 Schematic diagram of the characterization of the Cu@IrCuFeNiCoMo / CNTs core-shell nanocrystal catalyst in Comparative Example 2; high-angle annular dark-field transmission electron microscopy images are (a), (b) and (c), the X-ray diffraction pattern is (d), and the element distribution diagram is (e). Figure 4 Figure a shows nanocrystals with uneven sizes of hundreds of nanometers. Figure 4 The individual nanocrystals in the dark-field images in b and c are highly similar to the octahedral models with different orientations, demonstrating the generation of octahedral nanocrystals. Figure 4Figure e in the middle shows the unique morphology of the octahedron. The element mapping shows that copper is enriched in the octahedral core, while iridium, iron, nickel, cobalt, molybdenum and part of copper are located in the shell, indicating the formation of Cu core@IrCuFeNiCoMo high-entropy alloy shell octahedron. Figure 4 The X-ray diffraction pattern in (d) clearly shows two main crystalline phases, namely the FCC phase of Cu located in the core and the FCC phase of IrCuFeNiCoMo high-entropy alloy in the shell, which further proves the generation of Cu@IrCuFeNiCoMo octahedral nanocrystals.
[0064] The above findings indicate that Pd and Cu, as the main components of the icosahedral core of the PdCu@IrPdCuFeNiCoMo core-shell, play a key role in the icosahedral morphology, size and crystal phase distribution, which in turn profoundly affects the catalytic mechanism.
[0065] Performance Test:
[0066] Figure 5 Figure 1 is a characterization diagram of acidic OER performance; the polarization curves of the catalysts and the reference sample iridium dioxide in Example 1, Example 2, Comparative Example 1, Comparative Example 2 are (a), the overpotential comparison at different current densities is (b), the Tafel slope diagram is (c), the polarization curve normalized by the electrochemical active surface area is (d), 1.50V RHE The comparison of mass activity and specific activity is (e), and the electrochemical impedance spectrum is (f). Figure 5 As shown in Figures a and b, at 10 / 50 mA cm -2 Under the conditions of 2.5 Å / s, the acidic OER overpotential of the core-shell icosahedron is 251 / 307 mV, while the overpotential of the high entropy alloy nanocage is 235 / 282 mV, both of which are better than the comparative example and the reference sample iridium dioxide. At the same time, the core-shell icosahedron and high entropy alloy nanocage show lower Tafel slopes than the comparative example and the reference sample iridium dioxide, indicating faster reaction kinetics in the OER process ( Figure 5 c). At 1.50V RHE Under the same conditions, the core-shell icosahedron and high-entropy alloy nanocages showed 0.93 and 0.60 mA cm, respectively. ECSA -2 The specific activity ( Figure 5 d and e), with 1624 and 662A g Ir -1 Ultra-high quality activity ( Figure 5 In addition, Figure 5 The electrochemical impedance spectroscopy in (f) further demonstrates the superior OER activity of the core-shell icosahedron and high-entropy alloy nanocages.
[0067] Figure 6is a PEMWE performance characterization diagram; the schematic diagram of the PEMWE device is (a), and the polarization curves of the core-shell icosahedral seven-element metal nanocrystals in Example 1, the high entropy alloy nanocages in Example 2, and the reference sample iridium dioxide as anode catalyst are (b), 1.0 / 2.0 A·cm -2 Comparison of battery voltage at (c), 65℃@500mA·cm -2 The chronopotentiometry curve below is (d).
[0068] The iridium-based catalyst of the present invention is used as the anode (with a loading of 0.25 mg Ir cm -2 ), commercial platinum carbon as cathode (loading 0.30 mg Pt cm -2 ), assembled the PEMWE device ( Figure 6 (a). The polarization curve shows that ( Figure 6 b and c), at 1.0 / 2.0A cm -2 Under the condition of 500mA cm, the battery voltage of high entropy alloy nanocages reached 1.65 / 1.77V, and the battery voltage of core-shell icosahedron was 1.68 / 1.83V, both better than iridium dioxide's 1.75 / 1.93V. -2 @65℃, the high entropy alloy nanocage can operate stably for more than 900 hours ( Figure 6 d). It can be seen that the iridium-based catalyst in the present invention provides a feasible solution for the high activity and stability of acidic OER catalysts, which is crucial for the stable operation of PEMWE.
[0069] In the preparation method of the high entropy alloy nano-iridium-based catalyst of the present invention, when the amount of each substance and the conditions are within the range provided by the present invention, the obtained catalyst is similar to that of Example 1 and Example 2. For example, the molar ratio of the palladium acetylacetonate, copper acetylacetonate, iridium acetylacetonate, iron acetylacetonate, nickel acetylacetonate and cobalt acetylacetonate is (0.9-1.1): (0.9-1.1): (0.9-1.1): (0.9-1.1): (0.9-1.1): (0.9-1.1); the molar ratio of the palladium acetylacetonate to molybdenum hexacarbonyl is (0.036-0.04) mmol: (0.16-0.18) mmol; the molar mass ratio of the palladium acetylacetonate: glucose: carbon nanotubes: hexadecyltrimethylammonium chloride is (0.036-0.04) mmol: (95-105) mg: (52-60) mg: (95-105) mg; the mass volume ratio of the hexadecyltrimethylammonium chloride to oleylamine is (95-105) mg: (25-35) mL. The heating treatment refers to stirring at 255-265°C for 1.5-2.5 hours; the stirring speed is 600-700 rpm; the heating treatment refers to heating the mixture at 15-25°C·min under stirring. -1 The heating rate is from room temperature to 255-265°C, and then the temperature is kept at this temperature for 1.5-2.5 hours.
[0070] The mass ratio of the core-shell icosahedral nanocrystals to ferric chloride is (18-22): (145-155); the mass ratio of the core-shell icosahedral nanocrystals to polyvinyl pyrrolidone is (18-22): (245-255); the mass volume ratio of polyvinyl pyrrolidone to water in solution A is (245-255) mg: (10-15) mL. In solution B, the mass ratio of ferric chloride to potassium bromide is (145-155): (595-605); the mass volume ratio of ferric chloride to concentrated hydrochloric acid is (145-155) mg: (0.8-1) mL, and the mass fraction of concentrated hydrochloric acid is 36%; the mass volume ratio of ferric chloride to water is (145-155) mg: (17-19) mL. The heating and stirring temperature is 97-103° C., the heating and stirring time is 0.48-0.52 hours; the stirring speed is 780-840 rpm; and the ultrasonic mixing time is 19-21 minutes.
Claims
1. A high entropy alloy nano-iridium-based catalyst, characterized in that: including one or more of core-shell icosahedral nanocrystals or high entropy alloy nanocages; The core-shell icosahedral nanocrystals are prepared by the following method: In a protective atmosphere, a mixture obtained by mixing hexadecyltrimethylammonium chloride, oleylamine, glucose, carbon nanotubes and a transition metal salt is heated to obtain core-shell icosahedral nanocrystals, namely core-shell icosahedral PdCu@IrPdCuFeNiCoMo / CNTs; the heating treatment refers to stirring at 255-265° C. for 1.5-2.5 hours; the transition metal salt is palladium acetylacetonate, copper acetylacetonate, iridium acetylacetonate, iron acetylacetonate, nickel acetylacetonate, cobalt acetylacetonate and molybdenum hexacarbonyl; The high entropy alloy nanocage is obtained by the following method: dispersing the core-shell icosahedral nanocrystals in water containing polyvinyl pyrrolidone to obtain solution A; dissolving ferric chloride, potassium bromide and concentrated hydrochloric acid in water to obtain solution B; adding solution A to solution B, ultrasonically treating and mixing, and then heating and stirring to obtain the high entropy alloy nanocage; the heating and stirring temperature is 97 to 103° C., and the heating and stirring time is 0.48 to 0.52 hours.
2. The high entropy alloy nano-iridium-based catalyst according to claim 1, characterized in that: In the preparation of core-shell icosahedral nanocrystals, the heating treatment specifically refers to heating the mixture at 15 to 25°C·min under stirring. -1 The heating rate is from room temperature to 255-265°C, and then kept warm for 1.5-2.5 hours; In the preparation of core-shell icosahedral nanocrystals, the molar ratio of palladium acetylacetonate, copper acetylacetonate, iridium acetylacetonate, iron acetylacetonate, nickel acetylacetonate and cobalt acetylacetonate is (0.9-1.1): (0.9-1.1): (0.9-1.1): (0.9-1.1): (0.9-1.1): (0.9-1.1); the molar ratio of palladium acetylacetonate to molybdenum hexacarbonyl is (0.036-0.04) mmol: (0.16-0.18) mmol; the molar mass ratio of palladium acetylacetonate: glucose: carbon nanotube: hexadecyltrimethylammonium chloride is (0.035-0.04) mmol: (95-105) mg: (52-60) mg: (95-105) mg; the mass volume ratio of hexadecyltrimethylammonium chloride to oleylamine is (95-105) mg: (25-35) mL; In the preparation of high entropy alloy nanocages, the stirring speed is 780-840 rpm; the ultrasonic mixing time is 19-21 min.
3. The high entropy alloy nano-iridium-based catalyst according to claim 2, characterized in that: The heat preservation treatment time is 100 to 135 minutes; The mass ratio of glucose to carbon nanotubes is (95-105) mg: (53.6-59.6) mg; the mass volume ratio of hexadecyltrimethylammonium chloride to oleylamine is (95-105) mg: (28-32) mL; The molar ratio of palladium acetylacetonate, copper acetylacetonate, iridium acetylacetonate, iron acetylacetonate, nickel acetylacetonate and cobalt acetylacetonate is 1:1:1:1:1:
1.
4. The high entropy alloy nano-iridium-based catalyst according to claim 1, characterized in that: In the preparation of high entropy alloy nanocages, the mass ratio of the core-shell icosahedral nanocrystals to ferric chloride is (18-22): (145-155); the mass ratio of the core-shell icosahedral nanocrystals to polyvinyl pyrrolidone is (18-22): (245-255); the mass volume ratio of polyvinyl pyrrolidone to water in the solution A is (245-255) mg: (10-15) ml; In solution B, the mass ratio of ferric chloride to potassium bromide is (145-155):(595-605); the mass volume ratio of ferric chloride to concentrated hydrochloric acid is (145-155) mg:(0.8-1) mL, and the mass fraction of concentrated hydrochloric acid is 36%; the mass volume ratio of ferric chloride to water is (145-155) mg:(17-19) mL.
5. The high entropy alloy nano-iridium-based catalyst according to claim 1, characterized in that: In the preparation of core-shell icosahedral nanocrystals, the stirring speed is 600-700 rpm; In the preparation of core-shell icosahedral nanocrystals, the mixture is prepared by dissolving hexadecyltrimethylammonium chloride in oleylamine to obtain a hexadecyltrimethylammonium chloride mixed solution; glucose, carbon nanotubes and transition metal salts are mixed, and then ultrasonically mixed with the hexadecyltrimethylammonium chloride mixed solution to obtain a mixture; In the preparation of core-shell icosahedral nanocrystals, the protective atmosphere refers to removing oxygen from the mixture and introducing a protective gas; In the preparation of core-shell icosahedral nanocrystals, after the heating treatment, subsequent treatment is performed; the subsequent treatment refers to cooling, centrifugation, washing the precipitate with a cyclohexane / ethanol mixed solution; then the precipitate is soaked in an acetic acid ethanol solution, centrifuged, washed with anhydrous ethanol, and dried; In the preparation of high entropy alloy nanocages, the frequency of the ultrasound is 36 to 44 kHz; In the preparation of the high entropy alloy nanocage, after heating and stirring, subsequent treatment is performed; in the preparation of the high entropy alloy nanocage, the subsequent treatment is centrifugation, washing, and drying.
6. The high entropy alloy nano-iridium-based catalyst according to claim 5, characterized in that: In the preparation of core-shell icosahedral nanocrystals, the ultrasonic mixing time is 1.5 to 2.5 hours, and the ultrasonic frequency is 32 to 48 kHz; In the preparation of core-shell icosahedral nanocrystals, the "under protective atmosphere" specifically refers to evacuating, passing protective gas, evacuating again, passing protective gas, repeating the operation, removing oxygen from the mixture and keeping it in a protective atmosphere; the time for evacuating and passing protective gas is 4 to 6 minutes; In the preparation of core-shell icosahedral nanocrystals, during cooling and centrifugation, the centrifugal speed is 9600-10000 rpm, the cyclohexane / ethanol volume ratio is 1:4-6, and the number of washings is 2-5 times; The concentration of the acetic acid ethanol solution is 0.4-0.6 mol / L, and the soaking treatment conditions are: soaking at 40-60°C for 2.5-3.5 hours; the centrifugal speed after soaking is 8500-9500 rpm, the number of washings is 1-3 times, the vacuum drying temperature is 55-65°C, and the drying time is 11.5-12.5 hours; In the preparation of high entropy alloy nanocages, the centrifugal speed is 8800-9200 rpm, the washing times are 2-4 times, the vacuum drying temperature is 55-65° C., and the drying time is 11.5-12.5 hours.
7. The method for preparing the high entropy alloy nano-iridium-based catalyst according to any one of claims 1 to 6, characterized in that: The following steps are involved: S1) in a protective atmosphere, heating a mixture obtained by mixing hexadecyltrimethylammonium chloride, oleylamine, glucose, carbon nanotubes and a transition metal salt to obtain core-shell icosahedral nanocrystals, namely core-shell icosahedral PdCu@IrPdCuFeNiCoMo / CNTs; the heating treatment refers to stirring at 255-265° C. for 1.5-2.5 hours; the transition metal salt is palladium acetylacetonate, copper acetylacetonate, iridium acetylacetonate, iron acetylacetonate, nickel acetylacetonate, cobalt acetylacetonate and molybdenum hexacarbonyl; and / or, S2) dispersing the core-shell icosahedral nanocrystals in water containing polyvinyl pyrrolidone to obtain solution A; dissolving ferric chloride, potassium bromide and concentrated hydrochloric acid in water to obtain solution B; adding solution A to solution B, and mixing by ultrasonic treatment, and then heating and stirring to obtain high entropy alloy nanocages, i.e., high entropy alloy nanocages IrPdCuFeNiCoMo-NCs / CNTs; the heating and stirring temperature is 97 to 103° C., and the heating and stirring time is 0.48 to 0.52 hours; The high entropy alloy nano-iridium-based catalyst includes one or more of core-shell icosahedral nanocrystals or high entropy alloy nanocages.
8. Use of the high entropy alloy nano-iridium-based catalyst according to any one of claims 1 to 6 in electrocatalytic oxygen evolution reaction.
9. The use according to claim 8, characterized in that: The high entropy alloy nano-iridium-based catalyst is used in electrocatalytic OER in an acidic environment.
10. The use of the high entropy alloy nano-iridium-based catalyst in proton exchange membrane water electrolysis according to any one of claims 1 to 6, characterized in that: The high entropy alloy nano-iridium-based catalyst is used as an anode catalyst.
Citation Information
Cited By
Nickel-based noble metal multi-shell nanocage material as well as preparation method and application thereof
CN121776508A
A nickel-based noble metal multi-shell nanocage material and a preparation method and application thereof
CN121776508B